Pengaruh Good Public Governance dan Sistem Pengendalian Intern Pemerintah Terhadap Kualitas Laporan Keuangan (Studi Pada Organisasi Perangkat Daerah Provinsi Riau) - Sepriani; Arini; Gusmarila Eka Putri (P3M Politeknik Negeri Bengkalis, 2025)
This research aims to find out and test whether Good Public Governance and the Government's Internal Control System influence the Quality of Financial Reports in Regional Apparatus Organizations in Riau Province. This research used a sample of 90 respondents using a non-probability sampling technique, namely Purposive Sampling. The method used in this research is a quantitative method. The data collection techniques used in this research are Questionnaires. The research method used in this research is multiple linear regression, with the help of SPSS 26. The results of this research show that good public governance (X1) and the government's internal control system (X2) influence the quality of financial reports (Y). The better the implementation of good public governance, the better the quality of financial reports. Implementing the government's internal control system will have an impact on improving the quality of financial reports.